Forecast of the Committee on Forests and the Forest Industry - United Nations Economic Commission for Europe (United Nations, 2023)
This publication is the statistical supplement to the official statement by the Committee on Forests and the Forest Industry about the current and next year's forest products markets. The tables in the publication show detailed forest products production and trade forecasts by country for 2022 and 2023. The tables are generated based on official submission by more than 20 member States from Europe, North America and Eastern Europe, Caucasus, and Central Asia. The tables presented cover roundwood (logs, pulpwood and fuel wood), sawnwood (coniferous and non-coniferous), wood-based panels (plywood, particle board, OSB and fibreboard), pulp, paper and wood pellets. The Committee also collects data on over 30 individual products for many countries in the UNECE region.